The Orthodox Church and «Russian Dissolve»: reflecting on lessons of the past (Review of the book Firsov S. L. «A Time for War and a Time for Peace». The Orthodox Russian Church and the Civil War in Russia: Essays on History and Historiography) - V. V. Kalinovsky; A. S. Puchenkov (Омский научный вестник: Серия "Общество. История. Современность")
The article characterizes one of the last works of the famous St. Petersburg historian S. L. Firsov, specialist in the field of Church history and church-state relations. The publication is devoted to the history and historiography of the Orthodox Russian Church during the period of the revolution and the Civil War. It is noted that the historian emphasizes the importance of the religious factor for understanding the importance of the socio-political processes that took place at this controversial time. The main theses expressed in the monograph are considered, its strengths and weaknesses are named.